Profile of IHC Marker in Lung Tumours - Bhardwaj, Aparna; Petwal, Snigdha; Kumar, Rajnish; Kaushik, Sanjay; Kishore, Sanjeev (Annals of Pathology and Laboratory Medicine, 2019)
Background: Lung biopsy is crucial in histopathological subtyping and classification. However, making an accurate diagnosis in small biopsies can be challenging. This study was aimed to distinguish and classify lung tumors employing immunohistochemical markers TTF-1(thyroid transcription factor 1), Cytokeratin 5/6, Cytokeratin 20, AE1/3. Subsequently, prognostic value of different histological types of lung tumours was established employing Ki-67. Material & Methods A total of 52 clinically diagnosed cases of lung carcinoma over a period of two years were included in our study. Of these 2 cases were excluded from the study as they showed granulomas on histopathology. All the cases after being diagnosed on H&E were subjected to Immunohistochemistry (IHC). Statistical Analysis: The statistical analysis was done using SPSS for Windows 15.0 program. Specificity, sensitivity, positive predictive value, negative predictive value of all these IHC markers was statistically evaluated. Results Of 29 cases diagnosed as Squamous cell carcinoma (SCC) on H&E, 26 were CK5/6 positive on IHC. Of 4 cases diagnosed as Primary Adenocarcinoma (ADC) on H&E, 3 were TTF-1 positive. Four cases of poorly differentiated carcinoma diagnosed on H&E, 1 case was diagnosed as SCC and 2 cases as Metastatic ADC on IHC. Ki-67 was high in 82.8% cases of SCC and in 50% cases of ADC. The sensitivity and specificity of CK5/6 and TTF-1 was 100%, 57.1% and 100%, 96.7% respectively. Conclusion: Employing IHC markers either singly or in a panel is a useful adjunct to morphological features and clinical parameter in the diagnosis and management of lung tumour.